6(4D+1)=6D

Simple and best practice solution for 6(4D+1)=6D equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(4D+1)=6D equation:


Simplifying
6(4D + 1) = 6D

Reorder the terms:
6(1 + 4D) = 6D
(1 * 6 + 4D * 6) = 6D
(6 + 24D) = 6D

Solving
6 + 24D = 6D

Solving for variable 'D'.

Move all terms containing D to the left, all other terms to the right.

Add '-6D' to each side of the equation.
6 + 24D + -6D = 6D + -6D

Combine like terms: 24D + -6D = 18D
6 + 18D = 6D + -6D

Combine like terms: 6D + -6D = 0
6 + 18D = 0

Add '-6' to each side of the equation.
6 + -6 + 18D = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 18D = 0 + -6
18D = 0 + -6

Combine like terms: 0 + -6 = -6
18D = -6

Divide each side by '18'.
D = -0.3333333333

Simplifying
D = -0.3333333333

See similar equations:

| 7x-61=4x-7 | | 8x-5x+140=8x+75 | | 1/5(3r-4)2/5 | | EC=3x-16 | | 2c-6=4-8c | | 5n-8=43 | | 3×1/7 | | 54/78= | | -6(6x-12)=-72 | | (5+4i)+(-5-4i)= | | 40=2x-110 | | 2b=54 | | 8x^2+6x-12=0 | | (2x^(3/4))/(3x^4) | | LO*L=3 | | 11=12-c | | 14=-46-5x | | -19.5n+6.12=-19.9n | | 2sinx-4=-2sinx | | -19.5n+6.12=-19.9 | | 2.8-3.5r=1.5 | | -33=-11-2x | | 5W-3=2(W-3) | | a-5/10=2a-2.1 | | -16.6p-17.36=-4.8-15.8p | | -7t=40 | | (5-4i)+(-5-4i)= | | 3x+4=15x+8 | | -4+5(-x-9)=63 | | 4x=16x^2 | | 9=12+5x-(6x+7) | | 10h+16=9h |

Equations solver categories